The Role of National Civil Capital in Improving Underprivileged Women’s Businesses: An Islamic Economic Analysis - Rendi Rendi; Ferdiansyah Himawan (Brilliant International Journal Of Management And Tourism, 2025)
This study discusses the role and financing mechanism of PT Permodalan Nasional Madani (PNM) through the Membina Ekonomi Keluarga Sejahtera (Mekaar) program in improving the businesses and welfare of underprivileged women in Polewali Mandar Regency. The issues raised focus on how the financing program not only increases women's economic capacity but also reflects the core values of Islamic economics. The purpose of this study is to analyze the role of PNM Mekaar in empowering underprivileged women and to assess the extent to which the principles of justice ( al-'adl ), benefit ( al-ma ṣ la ḥ ah ), and mutual assistance ( at-ta'āwun ) are applied in its financing mechanism. The study uses a descriptive qualitative method with a field study approach through in-depth interviews, observation, and documentation of program facilitators and active clients. The results show that unsecured financing, group mentoring, and entrepreneurship training are effective strategies in strengthening capital access, business capacity, and social solidarity among underprivileged women. This practice aligns with the principles of maqā ṣ id al-sharī ʿ ah, particularly in safeguarding and developing wealth ( ḥ if ẓ al-māl ). However, the implementation of Islamic economic values in the Mekaar program is more substantive social than formal contractual, considering that PNM still operates within a conventional system. The conclusion of this study confirms that the Mekaar program is an economic empowerment model that integrates Islamic values practically and contextually, and contributes to strengthening women's economics based on justice and welfare.